Isolamento e identificação de compostos fenólicos em folhas de Eugenia uniflora L. - Carvalho, Ariadne Gomes (2013)
Eugenia uniflora L., known as pitangueira, is widely distrubuted in Brazil; its leaves are used in popular medicine as a treatment for diarrhea, fever, inflamation, hyperglycemia and hypertension. The pharmacological activities are due mainly to the phenolic compounds present in its leaves; therefore the aim of this work was to isolate these compounds. Powdered air-dried leaves were homogenized in 50% aqueous acetone. The filtrate was concentrated and extracted with ethyl acetate, yielding AcOEt fraction. The aqueous layer was lyophilized and after that dissolved in methanol to separate the soluble and the insoluble methanolic fractions. The ethyl acetate and methanol soluble fractions were subjected to repeated column chromatography over Diaion HP-20 and Sephadex LH-20. Isolated compounds were analyzed by NMR H1, C13, COSY, HSQC and HMBC (with variable temperature) and mass spectroscopy. The applied technique of temperature variation spectroscopy has proved to be extremely promising for identification of macrocyclic compounds, providing accurate data for not only elucidation but correction of previously described assignments. Two galloyl esters: 2,3-di-O-galloyl-β-D-glucose (26 mg), 1,2,3,4,6-penta-O-galloyl-β-D-glucose (92 mg) and two monomeric ellagitannins: 3-O-galloyl-4,6-HHDP-β-D-glucose (540 mg) and2-Ogalloyl- 4,6-HHDP-β-D-glucose (20 mg) were obtained. The methanol soluble fraction furnished three dimeric ellagitannins: oenothein B (770 mg), eugeniflorinD2 (260 mg) and camptothin A (56 mg). In addition to hydrolysable tannins, four flavonoids were also isolated and identified: quercetin-3-O-α-L-rhamnopyranoside (114 mg), kaempferol-3-O- α-L-rhamnopyranoside (80 mg), myricetin-3-O-α-L-rhamno-pyranoside(32 mg) and myricetin-3-O-(2"-O-galloyl)-α-L-rhamnopyranoside (97 mg).For the first time in this specie the following compounds were found 2,3-di-O-galloyl-β-D-glucose, 1,2,3,4,6- penta-O-galloyl-β-D-glucose, 3-O-galloyl-4,6-HHDP-β-D-glucose, 2-O-galloyl-4,6- HHDP-β-D-glucose, camptothin A, kaempferol-3-O-α-L-rhamnopyranoside, and myricetin-3-O-(2"-O-galloyl)-α-L-rhamnopyranoside. The methodology applied in this work allowed the isolation and identification of eleven phenolic compounds, in the near future they will be tested in several biological assays.